PENGARUH TEKNIK REEDUKASI TERHADAP STRES AKADEMIK PADA SISWA KELAS VIII - Ayuni, Dinda Tri; Astuti, Farida Herna; Sarilah, Sarilah (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
ABSTRACT Academic stress is one of the psychological problems frequently experienced by students at the junior high school level due to learning demands, pressure to achieve high grades, and expectations from both the school environment and family. If not properly addressed, this condition may lead to decreased learning motivation and students’ psychological well-being. This study aims to analyze the effect of the reeducation technique on the level of academic stress among eighth-grade students at SMPN 1 Sumbawa Besar in the 2024/2025 academic year. The study employed a quantitative approach using a pre-experimental design with a One Group Pretest–Posttest Design. The research subjects consisted of eight students selected through purposive sampling from a total population of 63 students based on the results of the initial academic stress assessment. The treatment was provided through group counseling services using the reeducation technique conducted in three sessions. Data were collected using an academic stress questionnaire based on a Likert scale, while data analysis was carried out using a t-test to compare scores before and after the treatment. The results of the analysis showed that the calculated t value was 7.84, which was higher than the t table value of 2.365 at a 5% significance level with 7 degrees of freedom. These findings indicate that the application of the reeducation technique has a significant effect in reducing students’ academic stress. Therefore, the reeducation technique can be considered an alternative intervention strategy in group counseling services to help students manage academic pressure more adaptively. ABSTRAK Stres akademik merupakan salah satu permasalahan psikologis yang sering dialami siswa pada jenjang sekolah menengah pertama akibat tuntutan belajar, tekanan nilai, serta ekspektasi dari lingkungan sekolah maupun keluarga. Kondisi tersebut apabila tidak ditangani secara tepat dapat berdampak pada menurunnya motivasi belajar dan kesejahteraan psikologis siswa. Penelitian ini bertujuan untuk menganalisis pengaruh penerapan teknik reedukasi terhadap tingkat stres akademik siswa kelas VIII di SMPN 1 Sumbawa Besar Tahun Pelajaran 2024/2025. Penelitian menggunakan pendekatan kuantitatif dengan desain pra-eksperimen berupa One Group Pretest–Posttest Design. Subjek penelitian berjumlah 8 siswa yang dipilih melalui teknik purposive sampling dari total populasi 63 siswa berdasarkan hasil pengukuran awal tingkat stres akademik. Perlakuan diberikan melalui layanan bimbingan kelompok dengan teknik reedukasi yang dilaksanakan dalam tiga sesi pertemuan. Pengumpulan data dilakukan menggunakan angket stres akademik berbasis skala Likert, sedangkan analisis data menggunakan uji t untuk membandingkan skor sebelum dan sesudah perlakuan. Hasil analisis menunjukkan nilai t hitung sebesar 7,84 lebih besar dibandingkan nilai t tabel sebesar 2,365 pada taraf signifikansi 5% dengan derajat kebebasan 7. Temuan ini menunjukkan bahwa penerapan teknik reedukasi memberikan pengaruh yang signifikan dalam menurunkan tingkat stres akademik siswa. Dengan demikian, teknik reedukasi dapat dipertimbangkan sebagai salah satu strategi intervensi dalam layanan bimbingan kelompok untuk membantu siswa mengelola tekanan akademik secara lebih adaptif.